Developing indica maintainer lines with intermediate amylose content by Wx functional microsatellite marker in rice - ZHOU Yi-feng; ZHAO Fei; REN San-juan; BAO Jin-song; SHEN Sheng-quan (浙江大学学报. 农业与生命科学版)
Genotypes of the 13 indica maintainer lines were detected by the Wx gene functional microsatellite marker “484/485”. The results showed that there was significant association between the Wx genotypes and amylose contents of rice. Analysis of progenies in the generations F1 to F3 derived from “Ⅱ-32B/Yixiang 1B” confirmed that “484/485” microsatellite marker was tightly linked to and cosegregated with rice amylose content. After carrying out marker-assisted selection in F2 generation, individual plants with the homozygous Wx- Ⅰ genotype selected from F3 generation reached as high as 93.5%. The phenotypes such as plant type, grain shape, chalkiness, transparency, gelatinization temperature, etc. were characterized either in the field or in the lab. Finally, a total of 114 target breeding lines with Wx- Ⅰ genotype, good plant types, slender grain type, low degree of chalkiness, high degree of transparency, intermediate gelatinization temperature and amylose contents were successfully obtained from the F6 generation. Ninety-two point one percent of the breeding lines had the amylose contents between 15% and 20%. Results of testcross showed that 74.5% of the breeding lines were maintainer lines. It is suggested that developing indica maintainer lines with intermediate amylose contents by Wx microsatellite marker is feasible and effective.